Interreligous Pedagogy Reflections and Applications in Honor of Judith A. Berling (Asian Christianity in the Diaspora, 2018)
This volume is a collection of essays by former students of Judith Berling based on her revolutionary interreligious pedagogy. Her pedagogy can be summarized as a student centered, collaborative, and engaging teaching and learning process sparked by various ways of boundary-crossing. In this enterprise, each chapter explores the importance of understanding and negotiating "differences" through dialogue. The authors provide theoretical frameworks for engagements across conventional borders, and explore how the collaborative teaching model can be utilized in various teaching settings. As an example of her dialogical approach, Judith Berling herself provides a response to the chapters.